Unusual cause of large intrathoracic mass in a young male of Bangladesh: A case report of giant intrathoracic lipoma & literature review - Rahman, S M Tajdit (Int J Surg Case Rep, 2020)
INTRODUCTION: Lipoma in the thoracic cavity is very rare, unlike any subcutaneous lipoma, and can often grow very large without showing any symptoms. CASE: We report a 42-year-old man having giant intrathoracic lipoma which was found incidentally during routine checkup and the first documented case of the such type in Bangladesh. This benign tumor occupied almost the entire left hemithorax, and it was resected successfully by thoracotomy. The postoperative period was uneventful except for prolonged chest drain. Histological analysis confirmed intrathoracic lipoma. DISCUSSION: Usually, patients with intrathoracic lipoma are asymptomatic. But since lipomas can grow to a large size, they may cause symptoms due to the compression effect. Lipoma should be considered a differential diagnosis of asymptomatic large intrathoracic mass, and imaging is the best method for initial identification. CONCLUSION: As intrathoracic lipoma typically grows very slowly over years without any symptoms and signs, late diagnosis is common. Complete surgical extirpation is needed to prevent further recurrence.